The application of the movement video analysis technology in the sports area - Xiao, X. (Applied Mechanics and Materials, 2014)
In this paper, the author starts from the literature reviews and the development and application of the video analysis technology software in the sports area, discussing the movement video collection, the processed and transformed digits from the computer software. Through the application of the first-line coaches and teachers in the sports teaching course, the athletes or students can see the technical action and tactical implementation effects, get the timely and accurate analysis information of which it will be beneficial to put the language style into the intuitive image, make the exchange for the coach or the students at the spot. In this way, the sports training and the teaching results will be greatly improved.